ANALYSIS OF FACTORS AFFECTING SATISFACTION OF SCIENCE AND TECHNOLOGY TEAM.THE CASE VIET NAM - Tran van , Trang; Hong Le, Doan; Thanh Truc, Nguyen; Thu Nguyen, Ho Bach (The journal of contemporary issues in business and government, 2024)
For the first time, this study outlines the concepts of science and technology human resources, analyzes and evaluates the strengths, weaknesses and causes of limitations of Vietnam’s science and technology human resources over 20 years. At the same time, propose solutions to comprehensively develop this team in the coming international integration period. These include: strengthening the system of organizations and apparatus, attracting talented people, developing the scale and quality of human resources in science and technology, and cooperating to commercialize research results and publish them internationally. With the desk research method, using secondary data, the authors have deeply analyzed the mechanisms and policies of management, use and development of science and technology human resources in Vietnam. The article uses a dialectical, positivist approach, compares experiences and contrasts the policies of modern scientific and technological human resource development to assess reality and upcoming requirements.